2023
DOI: 10.1001/jamanetworkopen.2023.13734
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Associations Between Modifiable Risk Factors and Alzheimer Disease

Abstract: ImportanceAn estimated 40% of dementia is potentially preventable by modifying 12 risk factors throughout the life course. However, robust evidence for most of these risk factors is lacking. Effective interventions should target risk factors in the causal pathway to dementia.ObjectiveTo comprehensively disentangle potentially causal aspects of modifiable risk factors for Alzheimer disease (AD) to inspire new drug targeting and improved prevention.Design, Setting, and ParticipantsThis genetic association study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…6,9,12,17,20,36-38 Our finding of a U-shaped association between HDL-C and dementia is consistent with a recent study reporting an association between genetically determined high HDL-C and risk of AD using Mendelian randomization (OR per 1 SD increase = 1.10, 95% CI 1.05–1.16). 39 Together, our results additionally support recent literature suggesting complex effects of HDL-C on many diseases and mortality. 14,40 Because HDL-C is nonlinearly associated with risk of cardiovascular disease, 14 HDL-C may be nonlinearly associated with dementia through this increased risk of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 89%
“…6,9,12,17,20,36-38 Our finding of a U-shaped association between HDL-C and dementia is consistent with a recent study reporting an association between genetically determined high HDL-C and risk of AD using Mendelian randomization (OR per 1 SD increase = 1.10, 95% CI 1.05–1.16). 39 Together, our results additionally support recent literature suggesting complex effects of HDL-C on many diseases and mortality. 14,40 Because HDL-C is nonlinearly associated with risk of cardiovascular disease, 14 HDL-C may be nonlinearly associated with dementia through this increased risk of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 89%
“…To address this, we carefully scrutinized the IVs for metabolites using the Phenoscanner V2 website, 3 to determine whether each SNP was linked to established risk factors of AD. According to the study conducted by Luo et al (2023), the following risk factors for AD were considered, including educational attainment (Stern et al, 1994), HDL cholesterol (Reitz et al, 2010), smoking (Barnes and Yaffe, 2011), body mass index (Buchman et al, 2005), diastolic blood pressure (Qiu et al, 2003), and systolic blood pressure (Kivipelto et al, 2005). If SNPs exhibited a relationship with the potential confounders at a significance level of p < 1 × 10 −5 , we conducted an additional IVW analysis after excluding these SNPs to affirm the stability and accuracy of our results.…”
Section: Confounding Analysis and Multivariable Mr Analysismentioning
confidence: 84%
“…89 However, recent MR evidence has provided limited and inconclusive evidence of causal relationships of the modifiable risk factors presented by the Lancet Commission with dementia. 90,91 This may be in part due to effects of survival bias, particularly for risk factors that are significantly associated with earlier mortality, as well as loss of power due to heterogeneity in both the dementia outcome measure and riskfactor exposures. A description of these issues relating to MR and the potential for ML to help alleviate some of these problems in dementia prevention research is discussed in detail in the genetics and omics article also included in this special issue.…”
Section: 22mentioning
confidence: 99%
“…Other MR studies have also shown causal relationships between cognitive ability, education, and dementia 89 . However, recent MR evidence has provided limited and inconclusive evidence of causal relationships of the modifiable risk factors presented by the Lancet Commission with dementia 90,91 . This may be in part due to effects of survival bias, particularly for risk factors that are significantly associated with earlier mortality, as well as loss of power due to heterogeneity in both the dementia outcome measure and risk‐factor exposures.…”
Section: Use Of ML To Understand Modifiable Risk Factors For Dementia...mentioning
confidence: 99%